Fear of GI Symptoms has an Important Impact on Quality of Life in Patients With Moderate-to-Severe IBS - Lackner, Jeffrey M; Gudleski, Gregory D; Ma, Chang-Xing; Dewanwala, Akriti; Naliboff, Bruce (The American journal of gastroenterology, 2014)
Because irritable bowel syndrome (IBS) is a functional medical condition for which there is no curative therapy, treatment goals emphasize relieving gastrointestinal (GI) symptoms and optimizing the quality of life (QOL). This study sought to characterize the magnitude of the associations between QOL impairment, fear of IBS symptoms, and confounding variables. Subjects included 234 Rome III-diagnosed IBS patients (mean age, 41 years, 79%, female) without comorbid organic GI disease who were referred to two specialty care clinics of an National Institutes of Health trial for IBS. Subjects completed a testing battery that included the IBS-specific QOL (IBS-QOL), SF-12 (generic QOL), the UCLA GI Symptom Severity Scale, the Visceral Sensitivity Index, Trait Anxiety Inventory, and Brief Symptom Inventory. Multiple linear regression was used to develop a model for predicting QOL. Data supported an overall model that included sociodemographic, clinical (e.g., current severity of GI symptoms), and psychosocial (e.g., fear of GI symptoms, distress, neuroticism) variables, accounting for 48.7% of the variance in IBS-QOL (F=15.1, P <0.01). GI symptom fear was the most robust predictor of IBS-QOL (β=-0.45 P <0.01), accounting for 14.4% of the total variance. Patients' fear that GI symptoms have aversive consequences, is a predictor of QOL impairment that cannot be fully explained by the severity of their GI symptoms, overall emotional well-being, neurotic personality style, or other clinical features of IBS. An understanding of the unique impact that GI symptom fears have on QOL can inform treatment planning and help gastroenterologists to better manage more severe IBS patients seen in tertiary care clinics.